THE INFLUENCE BETWEEN THE LENGTH OF RADIOGRAPHER WORKING TIME AND THE REDUCTION OF SALIVARY pH (Research on Radiographers at RSUD Ulin Banjarmasin and RSGM Gusti Hasan Aman Banjarmasin in 2017) - Noorma Noorma; Bayu Indra Sukmana; Debby Saputera (Dentino : Jurnal Kedokteran Gigi, 2018)
Background: Radiographer is a radiation worker in a field of investigations that uses x-ray radiation sources for health services. X-ray radiation can cause radiation effects for radiographers, patients, the environment and surrounding communities. Salivary glands are organs which susceptible to x-ray radiation. One of the effects caused by ionizing radiation is the decrease in salivary pH. Purpose: The purpose of this study was to analyze the effect of radiographers’ length of working time on salivary pH decrease due to exposure to x-ray radiation received by radiographers while working at RSUD Ulin Banjarmasin and RSGM Gusti Hasan Aman Banjarmasin. Methods: This research was an observational analytic study using cross-sectional design. The samples used in the study consisted of 18 respondents which were radiographers who did saliva taking with total sampling technique. Result: The salivary pH measurement results showed the mean value of salivary pH on the radiographer with the average of 7 years of working which has a decrease by 0.12 from the normal salivary pH of 6.70. The statistical analysis was done using parametric statistic test of Simple Linear Regression where significant value of p = 0,003. Conclusion: There is an influence between the length of radiographer working time and the reduction of saliva pH resulting from the exposure of x-ray radiation received by the radiographer while working at RSUD Ulin Banjarmasin and RSGM Gusti Hasan Aman Banjarmasin